Relief of Paroxysmal Sharp Pain and Allodynia in Postherpetic Neuralgia by Intravenous Selenium: A Case Report - Wu, Chung-Yi; Wang, Li-Kai; Lin, Yao-Tsung; Chen, Jen-Yin (Archives of Clinical and Medical Case Reports, 2021)
Postherpetic neuralgia (PHN) is a neuropathic pain. PHN patients experience various types of pain, suggesting multipathophysiologic mechanisms. Gabapentinoids are first-line therapy for PHN. However, PHN is often refractory to the treatment. Mechanisms of gabapentinoids on pain include altering calcium channels, inhibiting N-methyl-D-aspartate (NMDA) receptors and reducing inducible nitric oxide synthase (iNOS). Selenium mediates neuroprotection through modulating NMDA receptors and reducing iNOS. We reported that a PHN patient with a low normal selenium level received intravenous selenium as an add-on therapy to pregabalin and responded well. More studies are required to determine the analgesic effects of selenium on PHN.